Perbandingan Flexible Pavement dan Rigid Pavement pada Jalan Raya Timur Kaliwungu Kabupaten Kendal Provinsi Jawa Tengah (Indonesian Journal of Civil Engineering Study, 2024)
East Kaliwungu Main Road in Kendal Regency is one of the primary routes that has suffered considerable damage due to high traffic volumes, particularly from heavy vehicles. This study aims to analyze and compare the thickness and cost requirements of two pavement systems—flexible pavement and rigid pavement—based on the 2017 Bina Marga design guidelines. The input data include an average daily traffic (ADT) of 7,786 vehicles (in SMP units) and a subgrade CBR value of 6.66%. The design results indicate that the flexible pavement structure, with a design service life of 20 years, consists of a 4 cm AC-WC layer, a 6 cm AC-BC layer, a 10.5 cm AC-Base layer, and a 30 cm Class A aggregate base course, with a total construction cost of IDR 13,420,200,000.00. Meanwhile, the rigid pavement structure, designed for a 40-year service life, comprises a 28.5 cm cement concrete slab, a 10 cm lean mix concrete (LMC) subbase, and a 15 cm drainage layer, with a total construction cost of IDR 18,982,995,000.00. In terms of initial construction cost, rigid pavement requires a higher investment. However, it demonstrates greater resistance to heavy traffic loads and entails lower maintenance requirements over the long term.
Keywords: Cost Estimation; Flexible Pavement; Pavement Systems; Rigid Pavement; Traffic Loads